Upaya Meningkatkan Kerja Keras dan Prestasi Belajar IPA Siswa Kelas IV Pada Materi Gaya Menggunakan Metode Eksperimen - Winandika, Gigih; Aziza, Amalia Nurul (PANCAR, 2017)
The problem of this study is the still low attitude of students' hard work and their learning achievements in science lessons especially in style material. This study aims to improve the hard work and student achievement in Natural Sciences subjects through experimental methods. This type of research is classroom action research consisting of 2 cycles. The object in this study were all fourth grade students of Tinggarjaya 2 Elementary School, which amounted to 31 students consisting of 9 male students and 14 female students. The instruments used in data collection used tests / evaluations and observation sheets for teacher activities and student activities. The indicator in this study is that there is an increase in student hard work, which is marked by an increase in the average hard work from the first cycle to the next cycle, and learning achievement is successful if 85% have reached the KKM 70. The results show that through the experimental method can improve hard work and student achievement on science subjects. This can be evidenced by the increase in the average hard work of students from the first cycle of 7.12 which increased in the second cycle to 9.95. The average value of student learning achievement in the first cycle is 65.95 and the classical completeness is 67.74%, and the average cycle II is 86.61 and the classical completeness is 96.77%